Efektivitas Rational Emotive Behavior Theraphy (REBT) Meningkatkan Self Esteem pada Siswa Madrasah Aliyah Kota Medan - Maya Selvia; Alfin Siregar (Cetta: Jurnal Ilmu Pendidikan, 2023)
An individual's self-esteem can be thought of as an evaluation of himself provided by another individual and based on the individual's relationships with others. Self-esteem is the result of an evaluation carried out by a person as well as the treatment of others towards him. It is able to indicate the level at which individuals have confidence in themselves and are able to succeed and be useful. Self-esteem is the result of evaluations made by a person as well as the treatment of others towards him. People who struggle with their sense of self-worth are more likely to have unfavorable opinions and concepts about themselves. Lack of self-esteem will make it difficult to form relationships with others that are comfortable and beneficial for those involved in the relationship. The purpose of this research is to determine whether or not Rational Emotive Behavior Therapy (REBT) is effective in boosting the self-esteem of students in MAN 3 Medan's class XI. This study used a True Experiment design for quantitative research, and questionnaires based on Coopersmith's theory of self-esteem were used to gather data). Using a random sampling approach, 73 students from IPA 2 and IPS 2 in class XI at MAN 3 Medan were used as samples for this research, namely probability sampling (random sampling). Shapiro-Wilk is used to check for normalcy. Levene's test of variance was employed to check for homogeneity in this research. The independent t test was used to process the study data with the assistance of SPSS 26 software. The research revealed that compared to the control group, the experimental group's pupils benefited more from the REBT therapy in terms of their self-esteem after receiving the services